Electronic paste and preparation method and application thereof

By surface modification of the electronic paste composed of core-shell Ag/Cu nanoparticles and lead-free glass phase powder, the existing low-temperature cured electronic paste is solved, and the electronic paste with high conductivity and good leveling is achieved. It is suitable for applications such as high-precision sensors and wearable smart devices.

CN119724688APending Publication Date: 2025-03-28JINGDEZHEN INNOVIT NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510050967.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In applications such as high-precision sensors and wearable smart devices, existing low-temperature cured electronic pastes have insufficient conductivity, resulting in the inability to meet the demand for signal transmission speed and accuracy. At the same time, the low leveling of the glass phase makes it difficult for the slurry to form a flat and smooth surface.

Method used

Electronic slurry composed of surface modified core-shell Ag/Cu nanoparticles, lead-free glass phase powder, epoxy resin E51, terpineol, citric acid, polyethylene glycol and T31 curing agent, was prepared by sonication and drying with the glass phase powder, and combined with roll mill grinding to prepare an electronic slurry with a particle size of 5-10μm.

Benefits of technology

It improves the conductivity and adhesion strength of electronic paste, enhances the stability and leveling of the paste, and is suitable for semiconductor packaging and circuit boards, meeting the needs of high-precision signal transmission.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of electronic paste, and particularly relates to electronic paste and a preparation method and application thereof. The coating is prepared from the following components: surface modified core-shell Ag / Cu nanoparticles, glass phase powder, epoxy resin E51, terpilenol, citric acid, polyethylene glycol and an amine curing agent. According to the electronic paste disclosed by the invention, the N-acetyl-L cysteine modified core-shell Ag / Cu nanoparticles are used as a conductive component, so that the conductivity of the electronic paste can be improved, and meanwhile, the stability is kept. The modification method is helpful for reducing the oxidation of the nanoparticles, so that the electrical properties of the nanoparticles are maintained. The phenolic aldehyde amine (T-31) curing agent is introduced, so that the heat resistance of a cured product is improved, and the phenolic hydroxyl group is introduced, so that the curing reaction activity is enhanced, and the compatibility and affinity of the epoxy resin and an auxiliary material are improved. The electronic paste can be used in semiconductor packaging or circuit boards, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic pastes, and in particular relates to electronic pastes and a preparation method and application thereof. Background Art

[0002] In today's era of rapid technological development, flexible electronic circuits are gradually emerging as an emerging circuit form. It is a special circuit system constructed by cleverly placing electronic components on a flexible substrate. In the preparation process of flexible electronic circuits, low-temperature electronic paste plays an extremely critical role. This low-temperature electronic paste, which is composed of a polymer matrix and a conductive agent, has extremely broad application prospects, especially in the printing of flexible electronic circuits. It has shown unique advantages. Among them, electronic paste with copper powder as the conductive phase stands out in many application scenarios due to its relatively low cost and has been widely used.

[0003] With the continuous progress and innovation of science and technology, the performance requirements for flexible electronic circuits in various fields are also rising. Among them, the conductivity requirements for low-temperature curing electronic pastes used in flexible electronic circuits have been further improved. In some electronic devices with extremely high requirements for signal transmission speed and accuracy, such as high-precision sensors, wearable smart devices, etc., low-temperature curing electronic pastes are required to have stronger conductivity. This has prompted researchers to continuously explore new material formulas and preparation processes to improve the dispersibility and connectivity of conductive agents in electronic pastes, thereby improving overall conductivity. For example, by performing special surface treatment on copper powder, it can be more evenly distributed in the polymer matrix, reducing agglomeration, and thus enhancing the conductive properties of electronic paste. At the same time, new conductive additives are also being actively studied to work synergistically with copper powder to further optimize the conductive effect of electronic paste. Due to the high surface activity of conductive phase particles, their dispersion is poor and agglomeration is very likely to occur, which not only affects the uniformity of the paste, but also reduces its use efficiency. In addition, the low leveling problem of the glass phase is also more prominent, making it difficult for the paste to form a flat and smooth surface during application. These defects are intertwined, like heavy shackles, which have long seriously hindered the industrial development of high-temperature electronic pastes and made it difficult to use them on a large scale in actual production. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides an electronic paste and a preparation method and application thereof.

[0005] The present invention is achieved through the following technical solutions:

[0006] An electronic paste consists of the following components: surface modified core-shell Ag / Cu nanoparticles, glass phase powder, epoxy resin E51, pinene alcohol, citric acid, polyethylene glycol, and amine curing agent.

[0007] Furthermore, the amine curing agent is selected from T31 curing agent. The surface modified core-shell Ag / Cu nanoparticles are selected from N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles.

[0008] Furthermore, the method for preparing the N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles comprises the following steps:

[0009] Step 1: Add 5 mL of 0.1 mg / mL silver nitrate aqueous solution and 5 mL of 0.1 mg copper sulfate aqueous solution to 13 mL of 1.55 wt% PVP aqueous solution, stir at room temperature for 10 min, then add 1 mL of NH4OH, and then stir at room temperature for 15 min; then add 5 mL of 0.03 M NaBH4 dropwise, and then stir at room temperature for 1 h;

[0010] Step 2: Add 200 μL of 0.001M N-acetyl-L-cysteine ​​aqueous solution, and then add 1 mL of sodium citrate solution; then transfer to an ice bath and stir for 10 min, then add 250 μL of 10 mM silver nitrate solution and stir for 30 min; after centrifugation, wash the precipitate with deionized water and dry.

[0011] Furthermore, the glass of the glass phase powder is lead-free glass, and its composition includes Bi2O3 50% to 65%, B2O3 25% to 40%, ZnO 5%, Sb2O3 3.5% and Al2O3 1.5%.

[0012] Furthermore, the mass fractions of the N-acetyl-L-cysteine ​​surface modified core-shell Ag / Cu nanoparticles are 50-60 parts, glass phase powder is 5 parts, epoxy resin E51 is 10 parts, terpineol is 20 parts, citric acid is 5 parts, polyethylene glycol is 1 part, and T31 curing agent is 4 parts.

[0013] Furthermore, the mass fraction of the N-acetyl-L-cysteine ​​surface-modified core-shell Ag / Cu nanoparticles is 60 parts.

[0014] The present invention also provides a method for preparing an electronic paste, comprising the following steps: Step S1: pouring N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles into water and ultrasonicating them at an ultrasonic frequency of 25 KHz for 20 minutes, then filtering, and drying at 50 degrees Celsius for 12 hours to obtain dried N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles;

[0015] Step S2: Take lead-free glass powder and heat it to 1100 degrees Celsius for firing. After cooling, use zirconium balls to ball mill the glass powder. After ball milling, pass the glass powder through a 325-mesh sieve; soak the sieved glass powder in a 10wt% hydrochloric acid solution for 0.5h, then wash the glass powder with deionized water until the pH is neutral, and then dry it for later use; obtain glass phase powder;

[0016] Step S3: 50 parts of N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles, 10 parts of epoxy resin E51, 20 parts of pinene alcohol, 5 parts of citric acid, 1 part of polyethylene glycol, 4 parts of T31 curing agent, and 5 parts of glass phase powder are stirred at 50°C for 3 hours to obtain a mixed slurry, and the mixed slurry is ground by a roller mill to obtain an electronic slurry with a particle size of 5-10 μm.

[0017] The electronic paste of the present invention can be used in semiconductor packaging or circuit boards.

[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0019] Using N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles as conductive components can improve the conductivity of electronic pastes while maintaining stability. This modification method helps to reduce the oxidation of nanoparticles, thereby maintaining their electrical properties. The introduction of phenolic amine (T-31) curing agent improves the heat resistance of the cured product, and due to the introduction of phenolic hydroxyl groups, the curing reaction activity is enhanced, and the compatibility and affinity of epoxy resin with auxiliary materials are improved. Electronic pastes can be used in semiconductor packaging or circuit boards and have broad application prospects. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0021] In the present invention, N-acetyl-L-cysteine, CAS: 616-91-1; 3-mercaptopropionic acid, CAS: 107-96-0; mercaptosuccinic acid, CAS: 70-49-5; 12-mercaptododecanoic acid, CAS: 82001-53-4; 11-mercaptoundecanoic acid, CAS: 71310-21-9; all reagents are analytically pure, purchased from commercial products, and are not further processed. The lead-free glass powder is composed of the following main components (mass fraction, wt%): Bi2O3 50% to 65%, B2O3 25% to 40%, ZnO 5%, Sb2O3 3.5% and Al2O3 1.5%.

[0022] Example 1 (N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles)

[0023] A method for preparing an electronic paste comprises the following steps:

[0024] Step S1: pouring N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles into water and ultrasonicating them at an ultrasonic frequency of 25 KHz for 20 min, then filtering and drying at 50 degrees Celsius for 12 h to obtain dried N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles;

[0025] Step S2: Take lead-free glass powder and heat it to 1100 degrees Celsius for firing. After cooling, use zirconium balls to ball mill the glass powder. After ball milling, pass the glass powder through a 325-mesh sieve; soak the sieved glass powder in a 10wt% hydrochloric acid solution for 0.5h, then wash the glass powder with deionized water until the pH is neutral, and then dry it for later use; obtain glass phase powder;

[0026] Step S3: 50 parts of N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles, 10 parts of epoxy resin E51, 20 parts of pinene alcohol, 5 parts of citric acid, 1 part of polyethylene glycol, 4 parts of T31 curing agent, and 5 parts of glass phase powder are stirred at 50°C for 3 hours to obtain a mixed slurry, and the mixed slurry is ground by a roller mill to obtain an electronic slurry with a particle size of 5-10 μm.

[0027] The preparation method of the N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles is as follows:

[0028] Step 1: Add 5 mL of 0.1 mg / mL silver nitrate aqueous solution and 5 mL of 0.1 mg copper sulfate aqueous solution to 13 mL of 1.55 wt% PVP aqueous solution, stir at room temperature for 10 min, then add 1 mL of NH4OH, and then stir at room temperature for 15 min; then add 5 mL of 0.03 M NaBH4 dropwise, and then stir at room temperature for 1 h;

[0029] Step 2: Add 200 μL of 0.001M N-acetyl-L-cysteine ​​aqueous solution, and then add 1 mL of sodium citrate solution; then transfer to an ice bath and stir for 10 minutes, then add 250 μL of 10 mM silver nitrate solution and stir for 30 minutes; after centrifugation, wash the precipitate with deionized water and dry.

[0030] Example 2 (N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles)

[0031] A method for preparing an electronic paste comprises the following steps:

[0032] Step S1: pouring N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles into water and ultrasonicating them at an ultrasonic frequency of 25 KHz for 20 min, then filtering and drying at 50 degrees Celsius for 12 h to obtain dried N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles;

[0033] Step S2: Take lead-free glass powder and heat it to 1100 degrees Celsius for firing. After cooling, use zirconium balls to ball mill the glass powder. After ball milling, pass the glass powder through a 325-mesh sieve; soak the sieved glass powder in a 10wt% hydrochloric acid solution for 0.5h, then wash the glass powder with deionized water until the pH is neutral, and then dry it for later use; obtain glass phase powder;

[0034] Step S3: 55 parts of N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles, 10 parts of epoxy resin E51, 20 parts of pinene alcohol, 5 parts of citric acid, 1 part of polyethylene glycol, 4 parts of T31 curing agent, and 5 parts of glass phase powder are stirred at 50°C for 3 hours to obtain a mixed slurry, and the mixed slurry is ground by a roller mill to obtain an electronic slurry with a particle size of 5-10 μm.

[0035] The preparation method of the N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles is as follows:

[0036] Step 1: Add 5 mL of 0.1 mg / mL silver nitrate aqueous solution and 5 mL of 0.1 mg copper sulfate aqueous solution to 13 mL of 1.55 wt% PVP aqueous solution, stir at room temperature for 10 min, then add 1 mL of NH4OH, and then stir at room temperature for 15 min; then add 5 mL of 0.03 M NaBH4 dropwise, and then stir at room temperature for 1 h;

[0037] Step 2: Add 200 μL of 0.001M N-acetyl-L-cysteine ​​aqueous solution, and then add 1 mL of sodium citrate solution; then transfer to an ice bath and stir for 10 minutes, then add 250 μL of 10 mM silver nitrate solution and stir for 30 minutes; after centrifugation, wash the precipitate with deionized water and dry.

[0038] Example 3 (N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles)

[0039] A method for preparing an electronic paste comprises the following steps:

[0040] Step S1: pouring N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles into water and ultrasonicating them at an ultrasonic frequency of 25 KHz for 20 min, then filtering and drying at 50 degrees Celsius for 12 h to obtain dried N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles;

[0041] Step S2: Take lead-free glass powder and heat it to 1100 degrees Celsius for firing. After cooling, use zirconium balls to ball mill the glass powder. After ball milling, pass the glass powder through a 325-mesh sieve; soak the sieved glass powder in a 10wt% hydrochloric acid solution for 0.5h, then wash the glass powder with deionized water until the pH is neutral, and then dry it for later use; obtain glass phase powder;

[0042] Step S3: 60 parts of N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles, 10 parts of epoxy resin E51, 20 parts of pinene alcohol, 5 parts of citric acid, 1 part of polyethylene glycol, 4 parts of T31 curing agent, and 5 parts of glass phase powder are stirred at 50°C for 3 hours to obtain a mixed slurry, and the mixed slurry is ground by a roller mill to obtain an electronic slurry with a particle size of 5-10 μm.

[0043] The preparation method of the N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles is as follows:

[0044] Step 1: Add 5 mL of 0.1 mg / mL silver nitrate aqueous solution and 5 mL of 0.1 mg copper sulfate aqueous solution to 13 mL of 1.55 wt% PVP aqueous solution, stir at room temperature for 10 min, then add 1 mL of NH4OH, and then stir at room temperature for 15 min; then add 5 mL of 0.03 M NaBH4 dropwise, and then stir at room temperature for 1 h;

[0045] Step 2: Add 200 μL of 0.001M N-acetyl-L-cysteine ​​aqueous solution, and then add 1 mL of sodium citrate solution; then transfer to an ice bath and stir for 10 minutes, then add 250 μL of 10 mM silver nitrate solution and stir for 30 minutes; after centrifugation, wash the precipitate with deionized water and dry.

[0046] Comparative Example 1 (3-Mercaptopropionic acid modified core-shell Ag / Cu nanoparticles)

[0047] A method for preparing an electronic paste comprises the following steps:

[0048] Step S1: pouring 3-mercaptopropionic acid modified core-shell Ag / Cu nanoparticles into water and ultrasonicating them at an ultrasonic frequency of 25 KHz for 20 min, then filtering and drying at 50 degrees Celsius for 12 h to obtain dried 3-mercaptopropionic acid modified core-shell Ag / Cu nanoparticles;

[0049] Step S2: Take lead-free glass powder and heat it to 1100 degrees Celsius for firing. After cooling, use zirconium balls to ball mill the glass powder. After ball milling, pass the glass powder through a 325-mesh sieve; soak the sieved glass powder in a 10wt% hydrochloric acid solution for 0.5h, then wash the glass powder with deionized water until the pH is neutral, and then dry it for later use; obtain glass phase powder;

[0050] Step S3: 60 parts of 3-mercaptopropionic acid modified core-shell Ag / Cu nanoparticles, 10 parts of epoxy resin E51, 20 parts of pinene alcohol, 5 parts of citric acid, 1 part of polyethylene glycol, 4 parts of T31 curing agent, and 5 parts of glass phase powder are stirred at 50°C for 3 hours to obtain a mixed slurry, and the mixed slurry is ground by a roller mill to obtain an electronic slurry with a particle size of 5-10 μm.

[0051] The preparation method of the 3-mercaptopropionic acid modified core-shell Ag / Cu nanoparticles is as follows:

[0052] Step 1: Add 5 mL of 0.1 mg / mL silver nitrate aqueous solution and 5 mL of 0.1 mg copper sulfate aqueous solution to 13 mL of 1.55 wt% PVP aqueous solution, stir at room temperature for 10 min, then add 1 mL of NH4OH, and then stir at room temperature for 15 min; then add 5 mL of 0.03 M NaBH4 dropwise, and then stir at room temperature for 1 h;

[0053] Step 2: Add 200 μL of 0.001M 3-mercaptopropionic acid aqueous solution, and then add 1 mL of sodium citrate solution; then transfer to an ice bath and stir for 10 minutes, then add 250 μL of 10 mM silver nitrate solution and stir for 30 minutes; after centrifugation, wash the precipitate with deionized water and dry.

[0054] Comparative Example 2 (Mercaptosuccinic Acid Modified Core-Shell Ag / Cu Nanoparticles)

[0055] A method for preparing an electronic paste comprises the following steps: Step S1: pouring mercaptosuccinic acid modified core-shell Ag / Cu nanoparticles into water and ultrasonicating them at an ultrasonic frequency of 25 KHz for 20 minutes, then filtering, and drying at 50 degrees Celsius for 12 hours to obtain dried mercaptosuccinic acid modified core-shell Ag / Cu nanoparticles;

[0056] Step S2: Take lead-free glass powder and heat it to 1100 degrees Celsius for firing. After cooling, use zirconium balls to ball mill the glass powder. After ball milling, pass the glass powder through a 325-mesh sieve; soak the sieved glass powder in a 10wt% hydrochloric acid solution for 0.5h, then wash the glass powder with deionized water until the pH is neutral, and then dry it for later use; obtain glass phase powder;

[0057] Step S3: 60 parts of mercaptosuccinic acid modified core-shell Ag / Cu nanoparticles, 10 parts of epoxy resin E51, 20 parts of pinene alcohol, 5 parts of citric acid, 1 part of polyethylene glycol, 4 parts of T31 curing agent, and 5 parts of glass phase powder are stirred at 50°C for 3 hours to obtain a mixed slurry, and the mixed slurry is ground by a roller mill to obtain an electronic slurry with a particle size of 5-10 μm.

[0058] The preparation method of the mercaptosuccinic acid modified core-shell Ag / Cu nanoparticles is as follows:

[0059] Step 1: Add 5 mL of 0.1 mg / mL silver nitrate aqueous solution and 5 mL of 0.1 mg copper sulfate aqueous solution to 13 mL of 1.55 wt% PVP aqueous solution, stir at room temperature for 10 min, then add 1 mL of NH4OH, and then stir at room temperature for 15 min; then add 5 mL of 0.03 M NaBH4 dropwise, and then stir at room temperature for 1 h;

[0060] Step 2: Add 200 μL of 0.001M mercaptosuccinic acid modified core-shell Ag / Cu nanoparticle aqueous solution, and then add 1mL of sodium citrate solution; then transfer to an ice bath and stir for 10 minutes, then add 250 μL of 10mM silver nitrate solution and stir for 30 minutes; after centrifugation, wash the precipitate with deionized water and dry it.

[0061] Comparative Example 3 (12-Mercaptododecanoic acid)

[0062] A method for preparing an electronic paste comprises the following steps: Step S1: pouring 12-mercaptododecanoic acid into water and ultrasonicating it at an ultrasonic frequency of 25 KHz for 20 minutes, then filtering it, and drying it at 50 degrees Celsius for 12 hours to obtain dried 12-mercaptododecanoic acid;

[0063] Step S2: Take lead-free glass powder and heat it to 1100 degrees Celsius for firing. After cooling, use zirconium balls to ball mill the glass powder. After ball milling, pass the glass powder through a 325-mesh sieve; soak the sieved glass powder in a 10wt% hydrochloric acid solution for 0.5h, then wash the glass powder with deionized water until the pH is neutral, and then dry it for later use; obtain glass phase powder;

[0064] Step S3: 60 parts of 12-mercaptododecanoic acid, 10 parts of epoxy resin E51, 20 parts of pinene alcohol, 5 parts of citric acid, 1 part of polyethylene glycol, 4 parts of T31 curing agent, and 5 parts of glass phase powder are stirred at 50°C for 3 hours to obtain a mixed slurry, and the mixed slurry is ground by a roller mill to obtain an electronic slurry with a particle size of 5-10 μm.

[0065] The preparation method of the 12-mercaptododecanoic acid modified core-shell Ag / Cu nanoparticles is as follows:

[0066] Step 1: Add 5 mL of 0.1 mg / mL silver nitrate aqueous solution and 5 mL of 0.1 mg copper sulfate aqueous solution to 13 mL of 1.55 wt% PVP aqueous solution, stir at room temperature for 10 min, then add 1 mL of NH4OH, and then stir at room temperature for 15 min; then add 5 mL of 0.03 M NaBH4 dropwise, and then stir at room temperature for 1 h;

[0067] Step 2: Add 200 μL of 0.001M 12-mercaptododecanoic acid modified core-shell Ag / Cu nanoparticles aqueous solution, and then add 1 mL of sodium citrate solution; then transfer to an ice bath and stir for 10 minutes, then add 250 μL of 10 mM silver nitrate solution and stir for 30 minutes; after centrifugation, wash the precipitate with deionized water and dry it.

[0068] Comparative Example 4 (11-Mercaptoundecanoic acid)

[0069] A method for preparing an electronic paste comprises the following steps: Step S1: pouring 11-mercaptoundecanoic acid into water and ultrasonicating it at an ultrasonic frequency of 25 KHz for 20 minutes, then filtering it, and drying it at 50 degrees Celsius for 12 hours to obtain dried 11-mercaptoundecanoic acid;

[0070] Step S2: Take lead-free glass powder and heat it to 1100 degrees Celsius for firing. After cooling, use zirconium balls to ball mill the glass powder. After ball milling, pass the glass powder through a 325-mesh sieve; soak the sieved glass powder in a 10wt% hydrochloric acid solution for 0.5h, then wash the glass powder with deionized water until the pH is neutral, and then dry it for later use; obtain glass phase powder;

[0071] Step S3: 60 parts of 11-mercaptoundecanoic acid, 10 parts of epoxy resin E51, 20 parts of pinene alcohol, 5 parts of citric acid, 1 part of polyethylene glycol, 4 parts of T31 curing agent, and 5 parts of glass phase powder are stirred at 50°C for 3 hours to obtain a mixed slurry, and the mixed slurry is ground by a roller mill to obtain an electronic slurry with a particle size of 5-10 μm.

[0072] The preparation method of the 11-mercaptoundecanoic acid modified core-shell Ag / Cu nanoparticles is as follows:

[0073] Step 1: Add 5 mL of 0.1 mg / mL silver nitrate aqueous solution and 5 mL of 0.1 mg copper sulfate aqueous solution to 13 mL of 1.55 wt% PVP aqueous solution, stir at room temperature for 10 min, then add 1 mL of NH4OH, and then stir at room temperature for 15 min; then add 5 mL of 0.03 M NaBH4 dropwise, and then stir at room temperature for 1 h;

[0074] Step 2: Add 200 μL of 0.001M 11-mercaptoundecanoic acid modified core-shell Ag / Cu nanoparticles aqueous solution, and then add 1 mL of sodium citrate solution; then transfer to an ice bath and stir for 10 minutes, then add 250 μL of 10 mM silver nitrate solution and stir for 30 minutes; after centrifugation, wash the precipitate with deionized water and dry it.

[0075] Performance Testing

[0076] The electronic pastes of the embodiments and comparative examples were molded, with a screen of 325 mesh and a film thickness of 30 μm. After printing, they were cured at 400 degrees Celsius for 30 minutes, and the resistance and adhesion strength tests were performed.

[0077] Table 1 Performance test

[0078] Resistivity (Ω·cm) Adhesion strength (MPa) Example 1 5.4 18.3 Example 2 4.7 18.8 Example 3 4.3 19.2 Comparative Example 1 6.9 13.3 Comparative Example 2 6.2 13.8 Comparative Example 3 5.7 14.2 Comparative Example 4 5.5 12.8

[0079] As can be seen from Table 1, compared with Comparative Examples 1-4, although the ligands of the core-shell Ag / Cu nanoparticles of Examples 1-3 are different, the effect on the resistivity is small, and the adhesion strength of Examples 1-3 is better than that of Comparative Examples 1-4.

Claims

1. An electronic paste, characterized in that: The invention is composed of the following components: surface modified core-shell Ag / Cu nanoparticles, glass phase powder, epoxy resin E51, pinene alcohol, citric acid, polyethylene glycol and amine curing agent.

2. The electronic paste according to claim 1, characterized in that: The amine curing agent is selected from T31 curing agent.

3. The electronic paste according to claim 1, characterized in that: The surface modified core-shell Ag / Cu nanoparticles are selected from N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles.

4. The electronic paste according to claim 3, characterized in that: The preparation method of the N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles comprises the following steps: Step 1: Add 5 mL of 0.1 mg / mL silver nitrate aqueous solution and 5 mL of 0.1 mg copper sulfate aqueous solution to 13 mL of 1.55 wt% PVP aqueous solution, stir at room temperature for 10 min, then add 1 mL of NH4OH, and then stir at room temperature for 15 min; then add 5 mL of 0.03 M NaBH4 dropwise, and then stir at room temperature for 1 h; Step 2: Add 200 μL of 0.001M N-acetyl-L-cysteine ​​aqueous solution, and then add 1 mL of sodium citrate solution; then transfer to an ice bath and stir for 10 min, then add 250 μL of 10 mM silver nitrate solution and stir for 30 min; after centrifugation, wash the precipitate with deionized water and dry.

5. The electronic paste according to claim 4, characterized in that: The glass of the glass phase powder is lead-free glass, and its composition includes Bi2O3 50%-65%, B2O3 25%-40%, ZnO 5%, Sb2O3 3.5% and Al2O3 1.5%.

6. The electronic paste according to claim 5, characterized in that: The mass fractions of the N-acetyl-L-cysteine ​​surface modified core-shell Ag / Cu nanoparticles are 50-60 parts, glass phase powder is 5 parts, epoxy resin E51 is 10 parts, terpineol is 20 parts, citric acid is 5 parts, polyethylene glycol is 1 part, and T31 curing agent is 4 parts.

7. The electronic paste according to claim 6, characterized in that: The mass fraction of the N-acetyl-L-cysteine ​​surface modified core-shell Ag / Cu nanoparticles is 60 parts.

8. A method for preparing an electronic paste, characterized in that: The method comprises the following steps: step S1: pouring N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles into water for ultrasonication at an ultrasonic frequency of 25 KHz for 20 minutes, then filtering, and drying at 50 degrees Celsius for 12 hours to obtain dried N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles; Step S2: Take lead-free glass powder and heat it to 1100 degrees Celsius for firing. After cooling, use zirconium balls to ball mill the glass powder. After ball milling, pass the glass powder through a 325-mesh sieve; soak the sieved glass powder in a 10wt% hydrochloric acid solution for 0.5h, then wash the glass powder with deionized water until the pH is neutral, and then dry it for later use; obtain glass phase powder; Step S3: 50 parts of N-acetyl-L-cysteine ​​modified core-shell Ag / Cu nanoparticles, 10 parts of epoxy resin E51, 20 parts of pinene alcohol, 5 parts of citric acid, 1 part of polyethylene glycol, 4 parts of T31 curing agent, and 5 parts of glass phase powder are stirred at 50°C for 3 hours to obtain a mixed slurry, and the mixed slurry is ground by a roller mill to obtain an electronic slurry with a particle size of 5-10 μm.

9. Use of the electronic paste according to any one of claims 1 to 7 in semiconductor packaging or circuit boards.